Control de los ingresos corrientes en los cuerpos de bomberos de la provincia de El Oro. - Llumiluisa Cando, Mishel Nicole (My University, 2020)
Fire brigades comply with an arduous workforce, which is to protect citizens in fire-related incidents and in different types of emergencies. This research is carried out with the objective of identifying the different sources of income that the fire departments of the Province of El Oro perceive. The present constant work of an introduction in which the work of the fire department and the types of income are detailed that these perceive, the type of methodology that was used was qualitative descriptive documentary type based on the regulations that govern these entities, which we acquire current and real information possessed by said institution; Subsequently, there is the development of the investigation that details several technical terms and specifies the control of the current income followed by the conclusions reached with the preparation of this project.
Los Cuerpos de Bomberos cumplen con una ardua labor, que es proteger a los ciudadanos en incidentes relacionados con el fuego y en diferentes tipos de emergencias. Esta investigación se la realiza con el objetivo de identificar las diferentes fuentes de ingresos que perciben los cuerpos de Bomberos de la Provincia de El Oro. El presente trabajo consta de una introducción en la cual se detalla la labor del cuerpo de bomberos y los tipos de ingresos que estos perciben, el tipo de metodología que se empleó fue cualitativa tipo documental descriptiva en base a la normativa que rige a estas entidades, lo cual permitió adquirir información actual y real que posee dicha institución; posteriormente se encuentra el desarrollo de la investigación que detalla varios términos teóricos y especifica el control de los ingresos corrientes seguido de las conclusiones a las que se llegó con la elaboración de este proyecto.
Keywords: CUERPO DE BOMBEROS; CONTABILIDAD; INGRESOS CORRIENTES; CONTROL INTERNO; TIPOS DE INGRESO